The Influence Of Financial Distress On Stock Prices With Earnings Per Share As A Moderating Variable - Putri Nadya Salsabillah; Silvia Ashha Fajriyyah; Widiya Septiani; Maiyaliza Maiyaliza (Cita Konsultindo Research Center, 2024)
With Earnings Per Share (EPS) as a moderating variable, this study aims to determine whether financial distress affects stock prices. The Altman Z-Score model and construction companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 are used to assess the financial distress variable. This study uses secondary data and a purposive sampling approach to determine a sample from a population of 22 companies. Ultimately, this study finds that: (1) Financial distress does not have a significant effect on stock prices in the construction sector. This result is based on the significance value of the financial distress variable of 0.840, which is greater than 0.05. Thus, statistically, financial distress does not have a significant effect on stock prices. (2) When testing the moderating variable between financial distress and stock prices in construction sector companies, it is found that the EPS variable does not have an effect. This is based on the regression test value with MRA, which is 0.418 (the significance level is greater than 0.05).